Pregestational Diabetes and Congenital Heart Defects - Catarina Maduro; Luís Ferreira de Castro; Maria Lúcia Moleiro; Luís Guedes-Martins (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Studies have consistently shown a significant increase in the risk of congenital heart defects in the offspring of diabetic mothers compared with those of nondiabetic pregnancies. Evidence points that all types of pregestational diabetes have the capacity of generating cardiac malformations in a more accentuated manner than in gestational diabetes, and there seems to be an increased risk for all congenital heart defects phenotypes in the presence of maternal diabetes. Currently, the application of some therapies is under study in an attempt to reduce the risks inherent to diabetic pregnancies; however, it has not yet been possible to fully prove their effectiveness. The present review aims to better understand the mechanisms that govern the association between pregestational diabetes and congenital heart defects and how maternal diabetes interferes with fetal cardiac development, as there is still a long way to go in the investigation of this complex process.